Healthy and Smart Generation Program in Poverty Eradication - Sabinus Beni; Blasius Manggu; Yosua Damas Sadewo (Proceeding International Conference on Information Technology and Business, 2017)
The problem of poverty is still ensnare the Indonesian nation. Therefore, the government is moving to address the problem by issuing a continued reduction programs are Healthy and Smart Generation Program. The program is more focused on health and education is an important factor in influencing the level of welfare of a community. The problem of this research is how the match between the process of implementation of Healthy and Smart Generation Program 2016 conducted in the District Seluas Bengkayang with Operational Technical Guidelines. The concept used in this study is the evaluation. Type of this research is descriptive qualitative data. Informants consisted of: Chairman and Treasurer of the Project Management Unit, Facilitators, Fasilitator, Kader Village Community Empowerment, Regulatory and 5 beneficiaries. The evaluation of Healthy and Smart Generation Program in the district Shouts Bengkayang rated 5 stars indicators contained in the Technical Instructions of Operations, namely: the level of partiality to the poor, siding with women, concern for the future of children, transparency, accountability, participation and decentralization. The results of the evaluation in the District Seluas Bengkayang can be said to have not been successful, because there are still many who have not been in accordance with the Technical Guidelines OperationalKeywords: Poverty, Healthy, Smart.